Observational Instruments in the Arab Scientific Heritage Perspective Ismail ibn Heba Allah al-Hamawi | Al Alät Al Rosydiyyah fi At Thurost Al ‘Ilm Al ‘Aroby ‘Indä Ismäil ibn Hebä Allah al-Hämäwi - Elkhayati Rifai (Mantiqu Tayr: Journal of Arabic Language, 2021)
The article is an edited and critical study of an unpublished astronomical text entitled "The Astronomical Instrument Known as The Two-Pronged Machine" of a Damascene astronomer from the thirteenth century AD, Ismail ibn Heba Allah al-Hamawi. ancient scientific texts on this instrument are written by al-Kindi then Ibn Abbad and al-Nayrizi. Al-Kindi's text is the only text published from ancient texts, and today we present to researchers in the development of astronomical instruments a new text to contribute to enriching our knowledge of the scientific tradition of astronomical instruments in Islamic civilization.